Strategi Meningkatkan Kompetensi Mahasiswa Dibidang Akuntansi Melalui Metode Problem Based Learning Pada Politeknik Negeri Batam - Nanik Lestari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
This study aims to provide empirical evidence regarding the implementation of the Problem Based Learning (PBL) method in the Cost Accounting course, majoring in Business Management, Politeknik Negeri Batam. This research data used primary data and data collection techniques using a questionnaire which is distributed via the google from. The questionnaire was divided into 6 parts, namely the characteristics of the respondents, student attitudes, lecturers' responses to PIC PBL, time, reports and constraints in implementing PBL. The sample that was collected by the author was 55 respondents who were students who had taken cost accounting. The analytical method uses descriptive analysis. The results of this study are as follows: First, the implementation of PBL is a collaboration between the business management department, the engineering department and the electrical and mechanical department. The results of this collaboration obtained 17 products and services which were used as objects for implementing PBL with the output in the form of Cost of Production (HPP) for these objects. So the implementation of PBL was followed by 55 students and 17 lecturers of PIC PBL. Second, as many as 98% of students like or are interested in the topic or case study used during PBL and have been in accordance with the lecture contract or RPS. So as many as 98% are very enthusiastic about having discussions with their groups and the frequency of discussion was held more than 3 times. Third, Lecturers of PIC PBL in responding to students to make observations for less than 1 day or the same day were 73%. Likewise, as many as 93% of the completeness of data information, business processes and data accuracy provided by PBL PIC lecturers. Fourth, as many as 83% needed 3-5 weeks for the implementation of PBL. Fifth, overall (100%) the PBL reporting process uses templates and presentations as well as social media which can be used as a media for disseminating PBL information. Finally, the obstacles during the implementation of PBL are in the form of communication, cooperation, completeness of information and contribution / division of tasks between group members.